SERANGAN HAMA PENGGEREK DAUN PADA TEGAKAN DAMAR (Agathis alba) di NEGERI HUNITETU, KECAMATAN INAMOSOL, KABUPATEN SERAM BAGIAN BARAT - Wattimena, Cornelia M.A. (Universitas Nusa Bangsa, 2018)
Forest damage is not only caused by human activity, but can also be caused by other causes such as pest attacks. The purpose of this study was to determine the intensity and extent of leaf borer infestation in Damar stands in Hunitetu village of, Inomosol subdistrict, West Seram Regency. The method used in this study is the survey method. The results of the study showed that the leaves pests in the damar stands were green grasshopper (Atractomorpa crenulata) and snout beetles (Hylobius sp), with an intensity of damage of 11.00% for green grasshoppers (Atractomorpa crenulata) and 2.70% caused by snout beetles (Hylobius sp). Both are in the category of minor attacks. While the broadattack of green grasshopper's (Atractomorpa crenulata) of 50.20% belongs to category of severe attack and snout beetle (Hylobius sp), amounting to 43.89% belonging to the category of moderate attacks.